Synthesis of ï¡-Hydroxy ï¢-Proline: Potential for Organocataly-sis Reactions - T. Mohd Ali, M.; ., . (International Journal of Engineering and Technology, 2019)
A chiral organic molecule, L-proline catalyzed an enantioselective transformation reaction has becoming interesting synthetic protocol especially in the area of organocatalysis. Herein, a synthetic approach towards ï¡-hydroxy-ï¢-proline starting from bicyclic lactone lactam is hereby described. The syntheses utilized dicarboxylation reaction of bicyclic lacton lactam, followed by ether hydrolysis of the bicyclic ether and oxidation reaction of the primary alcohol. The synthetic strategy disclosed here allows further the enantioselective synthesis of a variety of unnatural amino acids based on ï¢-proline structure.Â